Strategies to Improve Vocational Graduate Employability: A Systematic Literature Review (2020-2025) - Lena Rusmiyati; Winda Dewi Listyasari; Mohammad Sofwan Effendi; Kamaludin Kamaludin (Research, Training and Philanthropy Institution Natural Aceh, 2026)
Digital transformation, workforce globalization, and Industry 4.0 require rapid adaptation in vocational education to prepare competitive graduates for the global labour market. This study identifies strategies to enhance vocational graduates' employability and maps thematic clusters and Research trends. We conducted a systematic literature review with a PRISMA bibliometric analysis. A search in Scopus and Google Scholar retrieved 400 records; after removing duplicates, screening, applying inclusion/exclusion criteria (peer-reviewed journals indexed in Scopus or SINTA 1–2, full text, relevance), and quality assessment, 44 articles (2020–2025) were analyzed. Bibliometric and thematic synthesis revealed five clusters: (1) digital transformation and Industry 4.0–oriented learning, (2) work-based learning and dual systems, (3) skills development and employability, (4) policy and governance, and (5) entrepreneurship and career development. Findings show that employability is strengthened by integrating technical and soft skills, fostering industry partnerships, improving digital literacy, enhancing teacher competence, and adopting adaptive governance. The study proposes an integrated framework linking digital transformation, learning, and governance, and offers evidence-based guidance for policymakers, institutions, and stakeholders to design responsive vocational strategies aligned with Industry 4.0.